A Needle, A Bobbin, A Strike: Women Needleworkers in America - Levine, Susan (Labour / Le Travail, 1986)
This article reviews the book, "A Needle, A Bobbin, A Strike: Women Needleworkers in America," edited by Joan M. Jensen & Sue Davidson.